Characterizing Afterslip and Ground Displacement Rate Increase Following the 2014 Iquique‐Pisagua Mw 8.1 Earthquake, Northern Chile. Issue 5 (7th May 2018) - Hoffmann, Felix; Metzger, Sabrina; Moreno, Marcos; Deng, Zhiguo; Sippl, Christian; Ortega‐Culaciati, Francisco; Oncken, Onno
Abstract: The 2014 Iquique‐Pisagua Mw 8.1 earthquake ruptured only parts of the 1877 Northern Chile‐Southern Peru seismic gap. Here we present a comprehensive analysis of 152 continuous and campaign Global Positioning System time series that captured more than a decade of interseismic loading prior to the event and 2 years of afterslip. In high spatiotemporal resolution, our data document upper plate response not only at the coseismically affected latitudes but also at the adjacent Loa plate segment to the south. Using a combination of elastic and viscoelastic half‐space models of different stages of the seismic cycle, we found that the highly coupled, former seismic gap contains a narrow low coupling zone at 21°S latitude. Just after the 2014 earthquake, this zone acts as a barrier impeding afterslip to continue southward. Possible reasons for this impediment could involve crustal heterogeneities or coupling discontinuities at the plate interface. After 2 years, afterslip cumulates to a maximum of ~89 cm and becomes negligible. Global Positioning System observations south of the inferred seismotectonic barrier reveal a deformation rate increase in the second year after the event. Our slip models suggest that this could be caused by a downdip coupling increase, perhaps bringing the highly coupled southern Loa segment closer to failure. Taken together, our results reveal (1) the interaction between different areas undergoing stress release and stress buildup in a major seismic gap, (2) constraints for the temporal variation of coupling degree in different stages of the seismic cycle, and (3) the influence of large earthquakes at adjacent segments. Key Points: GPS rates south of 21°S accelerate in the second year following the Iquique‐Pisagua event potentially reflecting coupling increase Afterslip lasts about 2 years before the interface relocks again almost entirely GPS velocity patterns and modeled interface afterslip rates suggest a seismotectonic barrier at 21°S